PUPUH KEKENDANGAN SEBAGAI IDENTITAS SEMAR PAGULINGAN SAIH LIMA PELIATAN - I Gde Made Indra Sadguna (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2011)
Semar Pagulingan Saih Lima (SPSL) is one kind of Balinese gamelan ensamble that still exist until now. In the village of Peliatan, there are three SPSL ensembles owned by Banjar Teges Kanginan, Tirta Sari group, and by individual. The SPSL repertoires in Peliatan were taught by three well-known artists such as I Nyoman Lotring, I Made Lebah, and I Made Gerindem. The gamelan SPSL in Peliatan is well-known because of internal and external factors. The internal factors are the gamelan itself, the tuning system, musical techniques, the members musical ability, and the music repertoars. The external factor is caused by the strong and wide networking in the local, national, and international areas. From this research, there are 11 kinds of pupuh kekendangan and seven angsels that are found. The 11 kinds of pupuh kekendangan are: pupuh kendang wangsit, kekilitan, sesimbaran, Asta Windu, ecet-ecetan, ngunda, ngelog, gemulung, ngetog malpal, dan pupuh kekendangan pekaad. Meanwhile the seven angsels which are found are: angsel genep, angsel numpuk, angsel penyalit, angsel ngantet, angsel ngetog, angsel narik, dan angsel kado. The pupuh kekendangan and angsels are used within the petegak and dance of the SPSL repertoires and becomes an important factor as the idenity within the SPSL in Peliatan. Â  Keywords: Semar Pagulingan Saih Lima, style, pupuh kekendangan, angselÂ